Beyond the control of the care home: A meta‐ethnography of qualitative studies of Infection Prevention and Control in residential and nursing homes for older people. (21st August 2021) - Daker‐White, Gavin; Panagioti, Maria; Giles, Sally; Blakeman, Thomas; Moore, Victoria; Hall, Alex; Jones, Paul P.; Wright, Oliver; Shears, Bethany; Tyler, Natasha; Campbell, Stephen
Abstract: Objective: This study aimed to develop interpretive insights concerning Infection Prevention and Control (IPC) in care homes for older people. Design: This study had a meta‐ethnography design. Data Sources: Six bibliographic databases were searched from inception to May 2020 to identify the relevant literature. Review Methods: A meta‐ethnography was performed. Results: Searches yielded 652 records; 15 were included. Findings were categorized into groups: The difficulties of enacting IPC measures in the care home environment; workload as an impediment to IPC practice; the tension between IPC and quality of life for care home residents; and problems dealing with medical services located outside the facility including diagnostics, general practice and pharmacy. Infection was revealed as something seen to lie 'outside' the control of the care home, whether according to origins or control measures. This could help explain the reported variability in IPC practice. Facilitators to IPC uptake involved repetitive training and professional development, although such opportunities can be constrained by the ways in which services are organized and delivered. Conclusions: Significant challenges were revealed in implementing IPC in care homes including staffing skills, education, workloads and work routines. These challenges cannot be properly addressed without resolving the tension between the objectives of maintaining resident quality of life while enacting IPC practice. Repetitive staff training and professional development with parallel organisational improvements have prospects to enhance IPC uptake in residential and nursing homes. Patient or Public Contribution: A carer of an older person joined study team meetings and was involved in writing a lay summary of the study findings.